A Real‐World Multicentre Retrospective Study of Paclitaxel‐Bevacizumab and Maintenance Therapy as First‐Line for HER2‐Negative Metastatic Breast Cancer. Issue 6 (30th November 2016) - Gamucci, Teresa; Mentuccia, Lucia; Natoli, Clara; Sperduti, Isabella; Cassano, Alessandra; Michelotti, Andrea; Di Lauro, Luigi; Sergi, Domenico; Fabi, Alessandra; Sarobba, Maria G.; Marchetti, Paolo; Barba, Maddalena; et al.
Abstract : Bevacizumab in combination with taxanes in HER2‐negative metastatic breast cancer (MBC) patients has shown improved progression‐free survival (PFS), despite the lack of clear overall survival (OS) benefit. We performed a retrospective analysis to evaluate the impact of paclitaxel‐bevacizumab and of maintenance therapy with bevacizumab (BM) and endocrine therapy (ET) in the real‐world practice. We identified 314 HER2‐negative MBC patients treated in 12 cancer centers. Overall, the median PFS and OS were 14 and 40 months, respectively. Among the 254 patients potentially eligible for BM, 183 received BM after paclitaxel discontinuation until progression/toxicity. PFS and OS were improved in patients who had received BM in comparison with those potentially eligible but who did not receive BM ( P < 0.0001 and P  = 0.001, respectively). Results were confirmed when adjusting for propensity score. Among the 216 hormone‐receptor positive patients eligible for BM, a more favorable PFS and OS were observed when maintenance ET was administered ( P  < 0.0001). Multivariate analysis showed that PS, BM, number of disease sites and maintenance ET were related to PFS, while response and maintenance ET were related to OS. In hormone‐receptor positive patients, BM produced a significant PFS and a trend towards OS benefit only in absence of maintenance ET ( P  = 0.0007 and P  = 0.06, respectively). In the triple‐negative subgroup, we observed a trend towards a better OS for patients who received BM ( P  = 0.06), without differences in PFS ( P  = 0.21). Our results confirmed the efficacy of first‐line paclitaxel‐bevacizumab in real‐world practice; both BM and maintenance ET significantly improved PFS and OS compared to no maintenance therapies. J. Cell. Physiol. 232: 1571–1578, 2017. © 2016 Wiley Periodicals, Inc. Abstract : We performed a retrospective analysis to evaluate the impact of paclitaxel‐bevacizumab and of maintenance therapy with bevacizumab (BM) and endocrine therapy (ET) in the real‐world practice. Our results confirmed the efficacy of first‐line paclitaxel‐bevacizumab in real‐world practice; both BM and maintenance ET significantly improved PFS and OS compared to no maintenance therapies.